Effect of Morpheme Meaning Dominance in Compound Word Recognition: Evidence from L2 Readers of Chinese - Yi Xu; Lin Chen (Languages)
In reading, rapid and reliable word recognition relies on high-quality representations at both the lexical and sublexical levels, with stable and flexible connections between form, sound, and meaning. Earlier studies suggested that meaning knowledge affects the formation and quality of orthographic representation in language learning, but the impact of morphemic meaning frequency on learners’ word recognition was not explored. This research examined second language (L2) Chinese readers’ recognition of compound words containing ambiguous morphemes. Using lexical decision tasks in a priming paradigm, we found that dominant primes (i.e., primes with morphemes encoding dominant meanings) facilitated L2 readers’ recognition of subordinate targets. We suggested that dominant meanings are associated with higher-quality orthographic representations in learners and dominant primes; thus, they facilitate readers’ recognition of orthographically and morphologically related subordinate targets. This study confirmed the role of sublexical constituents’ meaning variables in word recognition in language learning.